Gendered adversity and mental health of adolescents orphaned by AIDS in a rural South African community: An exploratory study. Issue 2 (4th March 2019) - Maepa, Mokoena P.; Ojedokun, Oluyinka; Idemudia, Erhabor S.; Morubane, Palesa
Abstract : This study explored gender differences in adversity and mental health among South African adolescents orphaned by AIDS. Adolescents ( N = 121; females = 45.5%; mean age 14.14 years, SD = 2.09) self-reported their childhood adversities and probable mental ill health on the Child Trauma and General Health Questionnaire. Results revealed that female participants orphaned by AIDS were significantly more likely to report childhood adversity at total score level as compared to male participants. However, both male and female participants reported comparable scores on subscales of childhood adversity (emotional abuse, physical abuse, sexual abuse, and physical neglect). Moreover, female participants displayed higher composite mental ill health and all its subscales except for social dysfunction. Our findings suggest that gender-sensitive programmes and policies to address the effect of childhood adversity and mental ill health among adolescents orphaned by AIDS, are urgently needed.